Hirayama disease - Chanabasappa V. Chavadi; Gowtham Jasti; Madhav Hegde; Anand Venugopal (Indian Journal of Neurosurgery)
Hirayama disease (HD) is a rare cause of cervical myelopathy often misdiagnosed as motor neuron disease and easily missed on routine magnetic resonance imaging (MRI), at time where detection is crucial to prevent irreversible cord injury. Believed to be a cervical flexion myelopathy, HD differs from motor neuron diseases because of its nonprogressive course and pathologic findings of chronic microcirculatory changes in the lower cervical cord. Dynamic forward displacement of dura in flexion causes asymmetric flattening of lower cervical cord. While dynamic contrast MRI is diagnostic, routine study has high predictive value. A case of HD, etiopathogenesis, imaging and treatment is summarized.